Clinical and Biological Insights into Combined Post-Capillary and Pre-Capillary Pulmonary Hypertension - Assad, Tufik R. (J Am Coll Cardiol, 2016)
BACKGROUND: Pulmonary hypertension (PH) is a common and morbid complication of left heart disease with 2 subtypes: isolated post-capillary PH (Ipc-PH) and combined post-capillary and pre-capillary PH (Cpc-PH). Little is known about the clinical or physiological characteristics that distinguish these 2 subphenotypes, and if Cpc-PH shares molecular similarities to pulmonary arterial hypertension (PAH). OBJECTIVES: We sought to test the hypothesis that the hemodynamic and genetic profile of Cpc-PH would more closely resemble PAH than Ipc-PH. METHODS: We used Vanderbilt’s electronic medical record linked to a DNA biorepository to extract demographics, clinical data, invasive hemodynamics, echocardiography, and vital status for all patients referred for right heart catheterization between 1998 and 2014. We identified shared genetic variants between PAH and Cpc-PH compared with Ipc-PH using pre-existing single-nucleotide polymorphism data. RESULTS: We identified 2,817 patients with PH (13% Cpc-PH, 52% Ipc-PH, and 20% PAH). Cpc-PH patients were on average 6 years younger, with more severe pulmonary vascular disease than Ipc-PH patients, despite similar comorbidities and prevalence, severity, and chronicity of left heart disease. After adjusting for relevant covariates, the risk of death was similar between Cpc-PH and Ipc-PH (HR: 1.14, 95% CI: 0.96 to 1.35, p = 0.15) when defined by diastolic pressure gradient. We identified 75 shared exonic single-nucleotide polymorphisms between Cpc-PH and PAH enriched in pathways involving cell structure, extracellular matrix, and immune function. These genes are expressed, on average, 32% higher in lungs relative to other tissues. CONCLUSIONS: Cpc-PH patients develop pulmonary vascular disease similar to PAH patients, despite younger age and similar prevalence of obesity, diabetes mellitus, and left heart disease compared with Ipc-PH patients. An exploratory genetic analysis in Cpc-PH identified genes and biological pathways in the lung known to contribute to PAH pathophysiology, suggesting that Cpc-PH may be a distinct and highly morbid PH subphenotype.